Effects of fertilizer type and harvesting age on species composition, yield and chemical composition of natural pasture in the highlands of Ethiopia - Shiferaw Yalew; Bimrew Asmare; Yeshambel Mekuriaw (Society for Indonesian Biodiversity, 2020)
Abstract. Yalew S, Asmare B, Mekuriaw Y. 2020. Effects of fertilizer type and harvesting age on species composition, yield, and chemical composition of natural pasture in the highlands of Ethiopia. Biodiversitas 21: 4999-5007. The experiment was conducted to evaluate the effects of fertilizer type and harvesting age on species composition, yield, and chemical composition of natural pasture in the highlands of Ethiopia. The experiment was laid out in randomized complete block design with factorial arrangement of two factors (fertilizer and harvesting age) with five replications. The data collected from the current study were forage species composition, dry matter yield, and chemical composition of natural pasture at different ages of harvesting. Forage species composition was determined by taking representative samples and identifying species from each sampling site. The samples of natural pasture were harvested at 90 and 120 days of age, weighed, dried, and then ground after that subsamples were taken for analyses of dry matter (DM), crude protein (CP), ash, acid detergent fiber (ADF), neutral detergent fiber (NDF) and acid detergent lignin (ADL). All the collected data were subjected to GLM ANOVA procedures of SAS version 9.0. The result indicated that all species composition and dry matter yield were significantly affected (P<0.001) by fertilizer type and harvesting ages. Higher forbs (0.66%) were found in control plot at 90 days of harvesting age. Natural pasture harvested at 120 days of harvesting and urea fertilizer application results the highest dry matter yield (DMY) (8.26 t/ha) while the lowest level (3.20 t/ha) from unfertilized plot at 90 and 120 days of harvesting. The relative proportion of legumes in the natural pasture attained its climax stage at 90 days while grass attained at 120 days of harvesting. The highest mean DMY (6.24 tone/ha) was obtained at 120 days of harvesting and the lowest (4.71 ton/ha) at 90 days of harvesting. Among the chemical composition parameters, DM, ash and CP were significantly affected (P<0.001) by both fertilizer type and harvesting age. The content of CP and ash were increased with manure fertilizer at early harvest age and were decreased with delayed harvest age. The application of fertilizer type did not significantly affect (P>0.05) NDF content of the natural pasture rather affected by stage of harvesting (P<0.001). Regardless of DM yield, better quality pasture was recorded for early (90 days) harvesting age and use of compost recommended for future natural pasture improvements as use of chemical fertilizer is relatively expensive for the majority of smallholder farmers in the highlands.